1963
DOI: 10.5962/bhl.title.6268
|View full text |Cite
|
Sign up to set email alerts
|

Temporal organization in cells; a dynamic theory of cellular control processes

Abstract: All Rights Reserved No part of this book may be reproduced in any form by photostat, microfilm, or any other means, without written permission from the pubhshers Library of Congress Catalog Number: 63-22091 PRINTED IN GREAT BRITAIN BY SPOTTISWOODE, BALLANTYNE AND CO. LTD LONDON AND COLCHESTER University as a post-doctoral fellow. It is a great pleasure for me to express my indebtedness to Professor C. H. Waddington for his encouragement in the pursuit of a theoretical study of biological processes, and for rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
4

Year Published

1964
1964
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 46 publications
2
135
0
4
Order By: Relevance
“…By reviewing the relevant literature it can be confirmed that most (if not all) authors have adopted a model of this form when attempting to fit changes in molecular concentrations to experimental data (see, for example [12,13,14]). In particular, if x 1 is chosen to represent the concentration of an mRNA transcript of protein x 2 , then it is common to assume linear protein expression rates (f 2 (x 1 ) = γx 1 with constant γ) and take f 2 (x 1 ) to be monotonically increasing or decreasing depending on whether x 2 is an activator or repressor, respectively.…”
Section: Two-component Feedback Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…By reviewing the relevant literature it can be confirmed that most (if not all) authors have adopted a model of this form when attempting to fit changes in molecular concentrations to experimental data (see, for example [12,13,14]). In particular, if x 1 is chosen to represent the concentration of an mRNA transcript of protein x 2 , then it is common to assume linear protein expression rates (f 2 (x 1 ) = γx 1 with constant γ) and take f 2 (x 1 ) to be monotonically increasing or decreasing depending on whether x 2 is an activator or repressor, respectively.…”
Section: Two-component Feedback Loopsmentioning
confidence: 99%
“…but since the coordinate change is a symmetry of the Hamiltonian 0 = ǫ{H, G} = ǫĠ (12) and therefore G is also conserved. The existence of conserved quantities is useful for qualitative study of complicated isolated systems, but these are rarely present in biological processes operating far from equilibrium.…”
Section: Review Of Q-deformed Classical Dynamics In One Dimensionmentioning
confidence: 99%
“…A mathematical treatment of this model by the techniques of statistical mechanics as outlined by Goodwin [2], predicts oscillatory phenomena in the protein synthesizing system. However, relatively few examples of such a phenomenon have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Friedman introduced Bayesian networks [4] as a probabilistic tool for the identification of regulatory data and showed that they can reproduce certain known regulatory relationships. Among the continuous models we can cite the ordinary differential equations model which was suggested several decades ago [5]. For a more detailed review about models of gene regulatory networks see [6].…”
Section: Introductionmentioning
confidence: 99%